PENGARUH STRATEGI PEMBELAJARAN PRAKTEK BERPASANGAN DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR FIKIH DI MTs SWASTA SIDIKALANG KECAMATAN SIDIKALANG KABUPATEN DAIRI TAHUN PELAJARAN 2018/2019 - Roslaeni, Syamsu Nahar, Chandra Wijaya (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2018)
Abstract: The aim of this research are (1) To knowing whether or not the influence of learning strategy thepractice pairs and the learning motivation to results the high leaning Fikih (2) whether or not the influenceof learning strategy the practice pairs and the learning motivation to results the low leaning Fikih (3) wheteror not influence the convensional strategy and the motivation of learning to results high learning Fikih (4)wheter or not influence the convensional strategy and the motivation of learning to results the low learningFikih (5) whether or not the interaction between the motivation to learn againts the results learning Fikih.This study is the kinds of the research experiment 2x2 Faktorial. The location of this research in MTsSwasta Sidikalang. The population of this research is all of the students in MTs Swasta Sidikang on 2018/2019 is 184 students and sample of this research take from class VII A and VII B is 50 students. Thetechniques collecting data using inquiries was covered with the Sclale Likert. The techniques data analysiscovering (1) Test validation and rehabilitas (2) Test normality and homogeneity (3) Analys ANAVA twoline. The product of this research is from product the results of the calculations statistics on variable theresults of learning Fikih on the students of class VII MTs Swasta Sidikalang with the category of high atfrequent intevals 79 – 91 as many as 7 people respondent (52%). That is in the can be evidenced by 52%.Then on the F count also can be see signifikansi on the table 0,000. It means that if we want to see theinteraction it turns out there are interaction between a strategy of learning practice pairs of the results oflearning students.Key Words: Strategy of learning practice pairs and Learning Motivation, to results thehigh leaning Fikih